A universidade aberta à terceira idade promovendo qualidade de vida : experiências de brasileiros e espanhóis - Derhun, Flávia Maria (2016)
Population aging and increased life expectancy raise the need to create and/or expand spaces capable of meeting the demands of the older population and, above all, promoting qualityof life. Thus, this study intended to understand how the Open University for the Third Age (UNATI) promotes the quality of life of Brazilian and Spanish elderly citizens. This was a qualitative study guided by the Grounded Theory and performed with elderly people linked to UNATI at the University of Barcelona ?Spain and to UNATI at the State University of Maringá ?Brazil. Data were collected from October 2014 to May 2015 for the Spanish and between December 2015 and June 2016 for the Brazilian citizens. We used a semi-structured script with closed questions about sociodemographic characterization, as well as about health and linkage with UNATI, and open questions concerning the perception of quality of life and benefits arising from their participation inUNATI. The inclusion criteria were: being aged 60 years or older and being registered in at least one subject in UNATI during the period of study. The interviews were recorded, fully transcribed and analyzed in such a way as to perform the second interview only after transcribing and analyzing the first one. A total of 44 elderly people took part in this survey, 22 of each institution. The adopted theoretical background was the Symbolic Interactionism. The analysis of data enabled the identification of a core phenomenon ?UNATI promoting quality of life?, which is explained by means of three categories: ?UNATI promoting autonomy and independence?, which addresses the strategies used by UNATI to preserve/improve functional and cognitive capacity and shows thecontinuous education as a way of emancipation of individuals. The category ?UNATI expanding social coexistence? depicts the university as a space for dialogue and exchange of experiences, as well as for creating friendship ties and experiencing interaction and learning, including in the intergenerational perspective. The integration between young and elderly in undergraduate curricular subjects highlighted UNATI as a place of learning and intergenerational interaction, of demystification of stereotypes, and was also full of barriers, such as the uncertainty of the elderly people with regard to the young generation and difficulties to follow the curricular content. The category ?Intellectual activities promoting welfare? reveals that the third age in UNATI was seen as a productive stage, surrounded by knowledge, information and enjoyable experiences, which were related to self-esteem, satisfaction and self-fulfillment for the elderly citizens. We have noted that, despite the study has been performed with elderly people of two different realities, the participation in university activities for the elderly citizens of both countries promoted quality of life by preserving autonomy and independence, by expanding social coexistence and by providing welfare with participation in intellectual activities. We hope to collaborate towards the consolidation of nursing as a science by overcoming the hindrances imposed in relation to old age so that it may be highlighted as a stage in which the individual remains active, participatory and valued as a person